Association between food insecurity and mental health outcomes among a convenient sample of Lebanese pregnant women - Rana Rizk; Maha Hoteit; Maroun Khattar; Yonna Sacre; Toni Sawma; Myriam El Khoury-Malhame (PLoS ONE, 2025)
Food insecurity (FI) is a pressing public health challenge, suggested to be associated with psychological distress and detrimental effects, especially in vulnerable populations such as pregnant women. To date, little is known in Lebanese pregnant women on the association between FI and emotional and behavioral outcomes. Thus, this study aimed to explore the association between FI, and emotional (anxiety, depression, distress) and behavioral (disordered eating, sleep quality) outcomes in a convenient sample of adult Lebanese pregnant women. A cross sectional study involving 146 pregnant women was conducted between 20 January 2023 and 16 September 2024. An online questionnaire was used to collect sociodemographic, financial, and medical characteristics. FI was assessed using the Arabic validated version of the Household Food Insecurity Access Scale, anxiety and depression using the Arabic validated version of the Patient Health Questionnaire, distress using the Beirut Distress Scale, disordered eating using the Arabic validated version of the Disordered Eating Attitudes in Pregnancy Scale, and sleep quality using the culturally-adapted Arabic version of the Pittsburgh Sleep Quality Index. Enter logistic regression models assessed the determinants of the dependent variables: anxiety, depression, distress, sleep quality, disordered eating. Findings showed that 66.4% of participants had FI, 50.7% had anxiety, 45% had depression, 83.6% reported high distress levels, 9.6% had disordered eating, and 57.5% had poor sleep quality. FI was associated with higher distress level, disordered eating, and poor sleep quality. No associations between FI and anxiety and depression were found. Given the high levels of FI and psychological distress in our sample, we emphasize the need for a comprehensive approach to support the physical and psychological health of pregnant women in Lebanon, with a focus on addressing underlying factors such as FI. Antenatal care must prioritize assessing food security and screening for and treating associated mental and behavioral health problems.